Investigating the Analytical Variability and Agreement of Manual Leukocyte Quantification Methods in Eastern Box Turtles (Terrapene carolina carolina) - Winter, John M.; Stacy, Nicole I.; Adamovicz, Laura A.; Allender, Matthew C. (Frontiers in Veterinary Science, 2019)
Leukogram evaluation provides valuable information about inflammation, infection, and stress in free-living and zoo-maintained wildlife. While multiple protocols for quantifying leukocytes are available in reptiles, agreement between methods is infrequently described and analytical variability (including repeatability and reproducibility) has not been critically evaluated. This study addresses these knowledge gaps for two hematological methods in eastern box turtles (Terrapene carolina carolina): Avian Leukopet™ (LO) and total white blood cell (WBC) estimates from blood films (EST). The objectives of this study were 1) to evaluate agreement in total WBC and individual leukocyte counts between the LO and EST methods, 2) to document repeatability (intra-assay variability) and reproducibility (inter-assay variability) for the LO method, and 3) to investigate whether biological drivers of WBC counts differ between quantification methods. Box turtles (n = 120) were sampled from five study sites in Illinois during the 2018 active season. The LO method produced significantly higher WBC counts than the EST method, and constant and proportional error was variable for each leukocyte type. The LO method demonstrated an intra-assay variability of 8.2% and an inter-assay variability of 12%, independent of biological variation. WBC counts were significantly affected by age class using both LO and EST methods, but WBC differences between locations and sexes were only observed using the LO method. These findings emphasize the importance of considering leukocyte determination method when analyzing reptilian hematology results. The inherent variability in currently available methods creates uncertainty in resulting data and highlights the need of a gold standard for reptilian WBC quantification.